Norway's Climate Odyssey: Assessing Impacts, Mitigation Strategies, and Policy Responses in a Warming Arctic - Jakob Oliver (International Journal of Science and Society, 2023)
Norway, a nation renowned for its dramatic landscapes, stands at the forefront of confronting the global climate crisis, particularly within the unique context of a warming Arctic. This article embarks on a comprehensive exploration of Norway's responses to the climate challenge, offering a nuanced assessment of climate change impacts, evaluation of mitigation strategies, and analysis of policy responses. The Arctic, with its iconic glaciers, fjords, and delicate ecosystems, bears witness to the unfolding narrative of climate transformation. Our assessment of climate change impacts reveals a landscape in flux, marked by melting glaciers, altered precipitation patterns, and shifting ecosystems. The article delves into the multifaceted implications of these changes, from their ecological consequences to their socio-economic effects on key sectors such as agriculture, fisheries, tourism, and infrastructure. Norway's proactive stance in mitigating climate change emerges through a rich tapestry of strategies. From the development of renewable energy sources to groundbreaking carbon capture and storage (CCS) projects, the nation has harnessed innovation and sustainability to navigate the path toward a low-carbon future. Emissions reduction targets, legislative frameworks, and international collaborations align Norway's climate policies with global agreements like the Paris Agreement.